1999
DOI: 10.1149/1.1392016
|View full text |Cite
|
Sign up to set email alerts
|

The Behavior of MCFCs Using Li/K and Li/Na Carbonates as the Electrolyte at High Pressure

Abstract: The molten carbonate fuel cell (MCFC) is an energy-producing electrochemical system which is expected to become commercial in the near future. High operating pressure, ca. 12-25 atm, is required to develop a highly efficient MCFC plant system combined with a gas turbine or coal gasifier system. However, pressurized performance over 10 atm has not been measured. It is important to study the performance of the MCFC at higher pressures than 10 atm from the viewpoint of developing a high-pressure system. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…In particular, Uchida's group has suggested that oxygen reduction in Li-K melts is a process of mixed diffusion of superoxide and CO 2 in the melts [22]. They analyzed cathodic overpotential with respect to the O 2 and CO 2 gas partial pressures and consistently concluded that the superoxide mechanism prevails under a normal condition of the Li-K carbonate single cells [23,24].…”
Section: Cathodementioning
confidence: 99%
“…In particular, Uchida's group has suggested that oxygen reduction in Li-K melts is a process of mixed diffusion of superoxide and CO 2 in the melts [22]. They analyzed cathodic overpotential with respect to the O 2 and CO 2 gas partial pressures and consistently concluded that the superoxide mechanism prevails under a normal condition of the Li-K carbonate single cells [23,24].…”
Section: Cathodementioning
confidence: 99%
“…The pressurized performance of Li/Na cells has also been investigated up to 4.5 MPa for more efficient plant operation, as shown in Fig. 3 [11]. Measured over a wider pressure range, the Li/Na cells have also shown greater performance than the Li/K cells.…”
Section: New Electrolyte Evaluationmentioning
confidence: 99%
“…3, the high pressure cell performance has been measured, and its applicability has also been demonstrated. Using the data obtained from high pressure operation, CRIEPI recently checked the effectiveness of the performance estimation equations for a wider range of pressure conditions [11]. Fig.…”
Section: High Pressure Operationmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, there are other e!ects of pressurization exerting a negative in#uence on the stack life. The biggest negative e!ect of pressurization known so far is the acceleration of cathode dissolution (Yoshikawa et al, 1999). The gas phase reaction is also known to favor the formation of methane.…”
Section: Generalized Pressurization Ewectsmentioning
confidence: 99%